Analisis Pengukuran Kinerja Pelayanan Kesehatan Ibu dan Anak dengan Metode BSC (Balance Scorecard) Menurut Perspektif Proses Bisnis Internal RSUD Mokoyurli Kabupaten Buol - Firman; Triyani Marwati; Siti Kurnia Widi; Sari Andini (Universitas Ahmad Dahlan, 2022)
Measuring the performance of Maternal and Child Health services is one of the key elements of the hospital which is an evaluation process as well as an obligation for the hospital every certain period. As a health service facility, performance is important to measure considering that MCH services include mandatory basic medical services. In order to analyze the performance of the Mokoyurli General Hospital, a Balanced Scorecard (BSC) is needed as a measuring tool. The problem of MCH in Indonesia is also a priority for the government. Maternal, Neonatal and Infant Mortality Rates obtained from the Buol District Health Office have a trend that is still fluctuating during 2017-2020. This type of research is qualitative research with a case study design. There were 38 research subjects who were divided into 30 questionnaire respondents and 8 interview respondents who represented each perspective, but specifically the internal business process perspective consisted of 5 people. Data analysis was carried out comparatively and using triangulation of sources and methods. Based on the results of the financial perspective, there are 2 KPIs that have been achieved and 1 that has not been achieved with an average score of 67%. From the consumer perspective, there are 3 KPIs and all three are achieved with an average score of 100%. Internal Business Process Perspective, there are 4 indicators that have been achieved and 1 indicator that has not been achieved with an average score of 80%, with details on the average BOR measurement tool, which is 60%. ALOS 4 days, TOI 3 days, NDR 11%, GDR 14%. The overall perspective of MCH performance at Mokoyurli Hospital has an average value of 85% where the 13 measuring instrument indicators used are 2 indicators that have not been achieved. Internal business process perspective measurement has an average value of 80% in good criteria as measured by BOR, ALOS, TOI, NDR and GDR.